Description verbale du mouvement dans le cadre de la typologie talmienne – une évaluation au croisement de deux paradigmes : le cognitivisme et l’enactivisme - Aurélie Barnabé (Anglophonia)
Relying on the Talmian typology, this investigation aims at assessing the linguistic behavior of French and English speakers, asked to describe entities in motion, in contexts where participants are submitted to different physical constraints pertaining to bodily experience. The emphasis on the results collected relates to the use of verbs describing motion events in the languages examined. The analysis of the corpora shows that the affiliation of a language to a specific language may be debated once speech is implemented in discursive contexts. Through the analysis of a non-linguistic variable, the speaker is apprehended, not as representing the world, but as enacting it. Language is not scrutinised through a representationalist dimension with the cognitive load it underlies, but is apprehended through the enactive paradigm through which a different reading of the linguistic data is suggested.